Increasing solvent polarity and addition of salts promote β-phase poly(vinylidene fluoride) formation - Low, Yuen Kei Adarina (2014)
This article investigates the effects of solvent polarity and salt addition on β-phase poly(vinylidene fluoride) (PVDF) formation. Films were solvent cast in aprotic solvents of varying polarities with or without salt addition. Characterization was done by Fourier transformed infra-red spectroscopy, differential scanning calorimetry, and scanning electron microscopy. Decreasing fractions of β-phase PVDF was observed with increasing drying temperature when less polar solvents were used. The most polar solvent (hexamethylphosphoramide) consistently produced films with at least 90.0% β-phase PVDF within the crystalline regions. Melting temperatures increased in correlation to absolute proportions of β-phase PVDF. Salt addition increased the formation of β-phase PVDF by 30%, with salts of higher valencies and smaller ionic radii resulting in more significant increases. Taken collectively, using solvents of higher polarities and addition of salts with high cationic valencies and small ionic radii will maximize β-phase formation in solvent cast PVDF films.